Telegami: um módulo de atividade gamificado para o moodle - Bezerra, Kleiton Lucas Lopes (Brasil, 2017)
The advancement of technology has made several changes in the educational scope provide tools and strategies for the teaching and learning process. Within this context, we have the Virtual Environments of Learning increasingly present in this educational process, helping in the management of educational contents and in the accompaniment of the students. These environments, for the most part, face a great difficulty: the low interaction of students with the environment. In most cases, students only access only when there is some evaluative activity or when they are required by the teacher and even then, few are the times whose interaction is motivated by their own individual desire to learn or by the sensation of pleasure in performing the activity proposed by the educator. Seeking a way to increase student interest in the teaching and learning process, a new approach has been gaining ground in the field of education by offering an alternative to generate and maintain students' motivation and engagement in the learning process. This approach is known as Gamification and proposes the use of elements present in digital games in non-gaming environments, in order to generate interest in a target audience. Following this perspective, the present work presents a tool that implements Gamification in a Virtual Learning Environment with the intention of making it more attractive for students. The environment chosen to receive the tool was Moodle. The proposal is to offer a tool with several elements of games to make the course more interesting for the students. To validate it, a mini-course was divided into two stages. At the end of the mini-course, a questionnaire was applied to obtain a qualitative evaluation, trying to evaluate if the application of the tool made the course more interesting. The responses were measured using the Likert scale, which specifies the level of agreement of the respondent with the question. This scale uses five levels of agreement ranging from total agreement to total disagreement
Keywords: Gamificação; Ambientes virtuais de aprendizagem; Educação; Processo de ensino e aprendizagem; Gamification; Virtual environments of learning; Education; Process of teaching and learning; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO